ANALISIS REALISASI PENCAPAIAN TARGET PENERIMAAN BEA DAN CUKAI PADA KANTOR PENGAWASAN DAN PELAYANAN BEA DAN CUKAI TIPE MADYA PABEAN BELAWAN TAHUN 2020-2021 - Anastasya, Tamara (Jurnal Manajemen Akuntansi dan Ilmu Ekonomi, 2024)
This research analyzes the realization of customs and excise revenue at the Belawan Intermediate Customs and Excise Supervision and Service Office. The results show that customs and excise have significant potential in optimizing state revenue, although they do not always increase annually. The decline in revenue is mainly due to fluctuations in international trade, with inconsistent monthly customs revenue. To boost revenue, this office has implemented joint programs, including joint analysis, joint collection, joint supervision, and cross-functional staff assignments, aimed at enhancing supervision of taxpayer compliance with customs and excise regulations. Additionally, revenue from excisable goods is relatively low, with only one instance of revenue recorded in 2020 and none in 2021.